Exploiting new GNSS signals to monitor, model and mitigate the ionospheric effects in GNSS - Elmas, Zeynep Günsu (2013)
Signals broadcast by the Global Navigation Satellite Systems (GNSS) enable global, autonomous, geo-spatial positioning exploited in the areas such as geodesy, surveying, transportation and agriculture. The propagation of these signals is affected as they propagate through the Earth's upper atmosphere, the ionosphere, due to the ionic and electronic structure of the ionosphere. The ionosphere, a highly dynamic and spatially and temporally variable medium, can be the largest error source in Global Navigation Satellite System (Klobuchar 1991) in the absence of the Selective Availability.